Somatic Mosaicism as Modulator of the Global and Intellectual Phenotype in Epimutated Angelman Syndrome Patients - Russo, Silvia; Mainini, Ester; Luoni, Chiara; Cogliati, Francesca; Giorgini, Valentina; Bonati, Maria Teresa; Forzano, Francesca; Termine, Cristiano; Murgia, Alessandra; Patrini, Mara; Fabretto, Antonella; Aldo, Skabar; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Angelman Syndrome (AS) is due to the loss of function of the single UBE3A gene, mapping to chromosome 15q11-q13 and encoding the E6AP ubiquitin ligase. Expression of UBE3A is subject to genomic imprinting which is restricted to the brain, where only the maternal allele is transcribed. AS pathogenetic mechanisms include deletion of the maternal 15q11-13 chromosomal region, chromosome 15 paternal uniparental disomy (UPD), Imprinting Defects (ImpD) leading to silencing of the maternal allele and intragenic mutations of the maternal UBE3A allele. From our AS cohort we sorted out for detailed clinical-molecular characterization six mosaic cases, five with ImpD epimutations and one with patUPD15. This latter case referred for intellectual disability and fortuitously solved by SNP array, is, to our knowledge, the unique patient reported with mosaic patUPD of this imprinted region. Somatic epimutation mosaicism represents a challenge for both clinical and molecular diagnostics. The described patients, referred to our center either for uncertain AS or simply for intellectual disability, could be molecularly characterized by applying a multi-method approach including Methylation-Sensitive PCR and MS-MLPA without a strict cut off. The percentage of normal cells detected ranged up to 40%. We confirm the mild phenotype reported in mosaic AS ImpD and provide a detailed analysis of IQ. Mild mental retardation, with significant difficulties in language expression, but only mildly impaired performance skills, together with pathognomonic EEG, is a cue not to overlook in mosaic AS patients. Mosaic epimutations should be searched also in patients with minor AS features and presenting only with intellectual disability.